Efect of heavy metals on the growth of the tropical microalga Tetrasermis chuii (Prasinophyceae) - Cordero, Jiudith (2005)
We determined the toxic effect of four metals, cadmium (Cd), copper (Cu), mercury (Hg) and lead (Pb), on the tropical microalga Tetraselmis Chuii (Butcher, 1959). We exposed 50 ml of cultivated microalgae (f/2 Guillard) in the exponential growth phase, with three replicates, to concentrations of 0 (control), 0.1, 1.0, 5.0, 10.0 and 20.0 mg.l -1 with each metal for 96 hr. We evaluated the lethal effect daily, through the cellular count. In the control treatment (not exposed to any metal) we observed an increase in cellular density. In all treatments exposed to metals, we observed a decrease in cellular density, which accelerated in 48 h, after which it became less pronounced. There were exceptions with low concentrations of Cd and Cu at 24 h, as there was no significant decrease, probably due to their use as micronutrients at these low concentrations. The metal that caused the most lethal effect was Pb, which killed 50% of the microalgal population at a concentration of 0.40 mg.l-1. This concentration was 3 times lower than that of mercury and 13 times lower than those of cadmium and copper. The microalga Tetraselmis chuii is recommended as a model species to estimate the toxic effects of xenobiotics on tropical seawaters environments.